2009
DOI: 10.3168/jds.2008-1978
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of susceptibility to clinical mastitis in Spanish Holstein cows

Abstract: This study had 3 objectives: to estimate genetic parameters and predict sires' transmitting abilities for clinical mastitis in a Spanish Holstein population, to propose a methodology for comparing models with different response variables by using a cost-based loss function, and to evaluate alternative genetic evaluation models by using this methodology. On-farm records for clinical mastitis from herds in 3 Spanish regions were analyzed as a binary trait (CM) and as number of episodes (NCM) per lactation. Linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 22 publications
2
37
0
4
Order By: Relevance
“…Comparisons of milk losses v. treatment costs as a proportion of total losses per CM case in different countries are summarized in Table 8. In this study and in those of some others, milk revenue losses accounted for a higher proportion of total mastitis costs than veterinary expenses (Kossaibati and Esslemont, 1997;Wolfova et al, 2006;Bar et al, 2008;Pé rez-Cabal et al, 2009). In contrast, veterinary costs made up a higher proportion of mastitis costs than milk losses in Denmark, India, Sweden and The Netherlands dairy herds (Nielsen 1994;Sasidhar et al, 2002;Wolfova et al, 2006;Svensson and Hultgren, 2008;Huijps et al, 2008).…”
Section: Comparison Estimates Of Economic Values For Scs By Three Metmentioning
confidence: 68%
“…Comparisons of milk losses v. treatment costs as a proportion of total losses per CM case in different countries are summarized in Table 8. In this study and in those of some others, milk revenue losses accounted for a higher proportion of total mastitis costs than veterinary expenses (Kossaibati and Esslemont, 1997;Wolfova et al, 2006;Bar et al, 2008;Pé rez-Cabal et al, 2009). In contrast, veterinary costs made up a higher proportion of mastitis costs than milk losses in Denmark, India, Sweden and The Netherlands dairy herds (Nielsen 1994;Sasidhar et al, 2002;Wolfova et al, 2006;Svensson and Hultgren, 2008;Huijps et al, 2008).…”
Section: Comparison Estimates Of Economic Values For Scs By Three Metmentioning
confidence: 68%
“…Estimates were generally higher when repeated cases of mastitis or lameness within parities were accounted for, as more variability is observed among cows. Definition, as either a binary or count trait, has been found to have differing impacts on sire rankings (Pé rez-Cabal et al, 2009;Vazquez et al, 2009), and it has been suggested that the definition should depend upon the selection goal. Pé rez-Cabal et al…”
Section: Genetics Of Fitness Traits In Dairy Cowsmentioning
confidence: 99%
“…So on the long term, consequences of CM for breeders are increasingly detrimental. Although management and hygiene practices on farms have a large impact on CM (Pérez-Cabal et al, 2009;Vazquez et al, 2012), genetic selection for mastitis resistance is also a solution to be considered for improvement of UH. For example, Nordic countries have included mastitis in their genetic evaluation since 1978 and have shown that improvement of resistance to mastitis as a result of genetic selection is effective (Heringstad et al, 2003).…”
Section: Introductionmentioning
confidence: 99%